Application of particle swarm optimization for solving optimal generation plant location problem / M. Y. Hassan ...[et al.] - Hassan, M. Y.; Suharto, M. N.; Abdullah, M. P.; Majid, M. S.; Hussin, F. (UiTM Press, 2012)
The global demand for energy especially in developing countries, has been witnessing a tremendous growth due to rapid population growth, economic growth and developing industrial sectors. Therefore, it is necessary to forecast the future energy needs and expand generation capacity to meet the increasing peak demand. This paper presents an optimization approach to determine the optimal location for installing a new generator in which the technical, economic and environmental aspects are all taken into consideration. The location that yields the minimum fuel costs, total emission and system loss is considered as the optimal generation plant location. The formulated objective function and its constraints compose an optimization problem is solved using particle swarm optimization (PSO). The proposed PSO based optimization approach is tested on IEEE 14-bus system and IEEE 30-bus system to illustrate the potential of the new approach. The simulation results have shown that the proposed approach is indeed capable of determining the optimal generation location that can save much overall fuel cost as well as reduce the total emissions of generators and losses in the network.